Novel high voltage gain dc–dc converter with dynamic analysis. Issue 3 (28th January 2021) - Ghaffarpour, Mohammad; Ebrahimi, Reza; Kojabadi, Hossein Madadi; Chang, Liuchen; Guerrero, Josep M.
Abstract: This study proposes a non‐isolated dc–dc converter based on a coupled inductor and switch‐capacitor–boosting techniques. The goal of the proposed topology is to increase the voltage gain with low‐duty cycle, so voltage stresses are decreased across power switches and diodes. The power switches are controlled by pulse width modulation. The common ground of input and output of the proposed converter makes it suitable for many applications such as photovoltaic systems. The proposed converter topology is discussed in continuous and discontinuous operation modes. A dynamic analysis of the proposed converter is also provided. Simulation and experimental verifications are presented to prove the effectiveness of the proposed topology.